PENCIPTAAN INFOGRAFIS TRANSFORMASI VISUAL GARUDA DI MEDIA SOSIAL - Wibawa, Mahendra (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2020)
One of the characters in Hindu mythology known as Garuda is closely related to the development of Indonesia’s visual culture. Visual transformations have occurred in the character of Garuda since the time of Indonesia’s independence to the present. As a visual cultural asset which rooted in the life of the Indonesian nation, comprehensive information about the transformation that occurs needs to be realized as one of the efforts to archive visual data and media that can be used for educational needs. This research will map the visual transformation of Garuda characters through graphic media contained in social media based on changes in visual elements and their anatomy and packaging them in media infographics. The anatomical analysis method was used in this study and followed by design using an illustrative approach. Key Words: Garuda, Visual Transformation, Anatomy, Infographic, Illustration.